2020
DOI: 10.1089/aid.2019.0282
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Alteration of Gut Microbiota: The Role of HIV Infection and Old Age

Abstract: Human immunodeficiency virus (HIV) infection results in gut microbiota alteration and this is associated with immune activation and chronic inflammation. The gastrointestinal tract is a primary site of viral replication and thus HIV-induced loss of T-helper (Th) cells in the gut causes impairments in intestinal barriers, resulting in disruptions in intestinal immunity and precipitating into gut dysbiosis. Here, we show that late HIV diagnosis can negatively affect the immunological, virological, and clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 62 publications
1
15
1
Order By: Relevance
“…This metabolic enmeshment with the host and other host-adapted commensals has led to the hypothesis that Akkermansia may represent a keystone species in the human gut 45 , 46 . In addition to the observation of increased prevalence of these beneficial bacteria with HIV, we also found that certain gammaproteobacteria, Haemophilus influenzae and an unassigned Enterobacteriaceae member, were decreased in children living with HIV in Cameroon, which is in contrast to previous reports in HIV-infected populations 47 . Taken together, these results suggest that certain aspects of the HIV-associated microbiome in these children would indicate a healthier microbiome.…”
Section: Discussioncontrasting
confidence: 86%
“…This metabolic enmeshment with the host and other host-adapted commensals has led to the hypothesis that Akkermansia may represent a keystone species in the human gut 45 , 46 . In addition to the observation of increased prevalence of these beneficial bacteria with HIV, we also found that certain gammaproteobacteria, Haemophilus influenzae and an unassigned Enterobacteriaceae member, were decreased in children living with HIV in Cameroon, which is in contrast to previous reports in HIV-infected populations 47 . Taken together, these results suggest that certain aspects of the HIV-associated microbiome in these children would indicate a healthier microbiome.…”
Section: Discussioncontrasting
confidence: 86%
“…The commensal microbiome forms a dynamic environment that can be altered and cause dysbiosis from virus infection but can be positively modulated by diet components and probiotic treatments. 113 , 114 , 115 Several studies show than an optimal immune response depends on proper diet and nutrition to control SARS-CoV-2 infection. 71 , 116 In general, malnutrition can compromise the immune response, therefore affecting the vulnerability of the response to COVID-19.…”
Section: Changes In the Gut Microbiota Composition Through Diet To Dementioning
confidence: 99%
“…Overall, changes to the gut microbiota during HIV infection are influenced by factors including ethnicity, sex, age, geography, dietary habits, lifestyle, operational factors, sample type and treatment (36)(37)(38)(39). In the present study, alterations in the intestinal mucosal microbiota and dysbiosis were identified in HIV-infected patients from Guangzhou, China.…”
Section: Discussionmentioning
confidence: 62%